Racism in Hidden Figures Movie Directed by Theodore Melfi - Unpris Yastanti; Sinta Isnia; Irwin Ananta Vidada (Center of Language and Cultural Studies, 2021)
The purposes of this research are to identity racism on three women in the movie, types of racism, and the effects of racism on victims in Hidden Figures Movie. This research used the descriptive qualitative method to analyze the data. This research was taken from a film called Hidden Figures. The results of this study reveal that: (1) Racism is the attitude of the majority who feel superior and great who consider themselves entitled to hold power and do negative things such as injustice, this does not only involve humans but also nature or the environment. Victims of this incident always feel alienated and helpless, (2) Types of racism treatment such as Personal Racism and Institutional Racism (3) Effects on victims who receive racism treatment such as motivation, fight for equal rights and inferior attitudes that feel insulted. (4) The results of this study also provide some moral messages from victims who face racism with a positive and negative attitude.